Isoliensinine confers neuroprotection and alleviates LPS-induced neuroinflammation in microglia by regulating the MAPK/NF-κB signaling - Yuan, Mengqin; Hu, Jinda; Gao, Lichen; Long, Wei; Wang, Sirui; Tan, Xinyue; Hu, Jinyue (Frontiers in Pharmacology, 2025)
BackgroundThe increasing aged population poses issues in the management of age-related disorders, notably Alzheimer’s disease (AD), which significantly affects the health and quality of life of seniors. Neuroinflammation is a significant factor in Alzheimer’s disease pathogenesis. Isoliensinine (ISO), a bisbenzylisoquinoline alkaloid derived from lotus seed embryos, exhibits antioxidant and anti-inflammatory effects. Nonetheless, its function in neuroinflammation has yet to be investigated.MethodsWe examined the impact of ISO on LPS-induced neuroinflammation in BV2 microglial cells by using biological tests. Western blotting confirmed ISO’s influence on MAPK/NF-κB signaling pathways. In addition, oxidative stress markers and JC-1 staining were employed to assess the impact of ISO on LPS-induced oxidative stress and mitochondrial dysfunction in BV2 cells.ResultsISO markedly diminished LPS-induced neuroinflammation in BV2 cells through the modulation of the MAPK/NF-κB pathway. Conditioned media derived from ISO-treated BV2 cells enhanced the vitality of HT-22 cells. ISO also alleviated oxidative stress and mitochondrial dysfunction.ConclusionOur findings indicate that ISO mitigates neuroinflammation by inhibiting MAPK/NF-κB signaling and provides neuroprotection by diminishing oxidative stress and mitochondrial impairment. These effects collectively enhance its neuroprotective capacity, indicating that ISO may represent a potential candidate for further investigation in AD.